2016
DOI: 10.3892/mco.2016.758
|View full text |Cite
|
Sign up to set email alerts
|

Pemetrexed and bevacizumab-containing chemotherapy for pleomorphic carcinoma of the lung

Abstract: Abstract. Pleomorphic carcinoma of the lung is a rare, highly malignant subtype of lung cancer, with a more aggressive clinical course compared with other types of non-small-cell lung cancer (NSCLC). Pemetrexed and bevacizumab are currently evaluated as two of the most reliable chemotherapeutic drugs for advanced NSCLC. We herein report a case of a 68-and a 46-year-old man with recurrent and chemo-naïve pleomorphic carcinoma of the lung, respectively, who were treated with a combination of carboplatin, pemetre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Since then, new chemotherapeutic agents have been approved and supportive treatment developed to reduce the effects of adverse reactions has improved treatment response. Tamura et al reported relatively long-term survival in two PPC patients treated with a carboplatin, pemetrexed, bevacizumab regimen (24), and Lee et al reported strong responses to treatment with mesna, doxorubicin, ifosfamide, and dacarbazine (MAID) in two platinum-refractory PPC patients (25).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, new chemotherapeutic agents have been approved and supportive treatment developed to reduce the effects of adverse reactions has improved treatment response. Tamura et al reported relatively long-term survival in two PPC patients treated with a carboplatin, pemetrexed, bevacizumab regimen (24), and Lee et al reported strong responses to treatment with mesna, doxorubicin, ifosfamide, and dacarbazine (MAID) in two platinum-refractory PPC patients (25).…”
Section: Discussionmentioning
confidence: 99%